2014
DOI: 10.1638/2013-0290.1
|View full text |Cite
|
Sign up to set email alerts
|

COMPUTED TOMOGRAPHY AND MAGNETIC RESONANCE FOR THE ADVANCED IMAGING OF THE NORMAL NASAL CAVITY AND PARANASAL SINUSES OF THE KOALA (PHASCOLARCTOS CINEREUS)

Abstract: The objective of this study is to describe computed tomography (CT) and magnetic resonance (MR) for the cross-sectional imaging of the normal anatomy of the nasal cavity and paranasal sinuses of the koala (Phascolarctos cinereus), to provide reference figures for gross anatomy with corresponding CT and MR images and to compare the features of the nasal cavity and paranasal sinuses of the normal koala with that reported in other domestic species. Advanced imaging can be used to aid in diagnosis, to plan surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To the best of the authors' knowledge, this is the first description of this region in the sixbanded armadillo using anatomical cross-sections and conventional CT equipment. Similar studies accomplished on a variety of species, such as rhinoceros iguanas [12], horses [27,29], dogs [28,34], koalas [31], rabbits [32], and guinea pigs [33], have effectively demonstrated that the combination of advanced imaging techniques and anatomical cross-sections is adequate for studying the complex anatomy of this region.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…To the best of the authors' knowledge, this is the first description of this region in the sixbanded armadillo using anatomical cross-sections and conventional CT equipment. Similar studies accomplished on a variety of species, such as rhinoceros iguanas [12], horses [27,29], dogs [28,34], koalas [31], rabbits [32], and guinea pigs [33], have effectively demonstrated that the combination of advanced imaging techniques and anatomical cross-sections is adequate for studying the complex anatomy of this region.…”
Section: Discussionmentioning
confidence: 85%
“…However, the use of these techniques in exotic animal medicine is currently limited because of their expenses, availability, and the logistic problems of acquiring images of some of these species. Although descriptions of the CT and MRI of the nasal cavities and frontal sinuses have been done in exotic and traditional species, including dogs, horses, sea turtles, rabbits, koalas, guinea pigs, and members of the Dasypodidae family, such as the nine-banded armadillo [12,21,[27][28][29][30][31][32][33][34], a detailed anatomic description of those images of the normal six-banded armadillo is lacking. Therefore, the present study was conducted to shed light on the anatomical details of the six-banded armadillo's nasal cavity using anatomical cross-sectional images and their correlation with transverse CT images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation